Transitivity Analysis of Presidents' Speech on Economy - Hifni Hillah Hanafiyah; Marwito Wihadi; Nida Amalia Asikin (Journal of Applied Linguistics, 2025)
The purpose of this study was to identify the types of transitivity process found in Jokowi and Joe Biden's Speech on economy and to identify the similarities and differences in transitivity processes, used by the two presidents. The methodology that was used in this study was qualitative research method, and the research design is case study. The instrument was the researcher. This study found 67 major clauses in Jokowi's speech and 244 major clauses in Joe Biden's speech. Then the clauses were identified into six transitivity processes, in Jokowi's speech only 5 of the 6 transitivity processes were found, there’s no behavioral process in it. Meanwhile, in Joe Biden's speech all of the process types were found. The similarities were the dominant process which was material process and existential processes as the least process. The differences were there’s no behavioral process in Jokowi’s speech and huge gap of the using of mental process. The result can be interpreted that the goal of politics is to gain authority to implement certain political, economic, and social concepts. Here, language plays a major role in how each politician uses language to advance their political agenda through speech. Keywords : SFL, Transitivity, Speech Analysis.